The Trends of Biology Education Research from 2000 to 2017: A Content Analysis for the Thesis of Pre-Service Teachers - Haviz, M; Dewi, Asma; Putri, Arlita Laras; Wahyuni, Asri; Fajar, Najmiatul; Lufri, Lufri (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This study aims to investigate the trend of biological education research (BER) from 2000 to 2017 in the thesis of pre-service biology teachers. This study conducted a series of content analyses of the thesis from two universities. A total 1347 thesis were analyzed in terms of sample, method, design, elements and topics and subject matter. It was found that junior and senior high school were the most popular research sample trends. This study was also found that quantitive, research and development or/and educational design research became the trend of the method most chosen and conducted by preservice biology teachers. This findings were also indicated that descriptive, experimental, and 4-D were design trends chosen by preservice biology teachers. This study was also found that cognitive and media of learning were the research elements are the most chosen and conducted by preservice biology teachers. The next findings showed that system and cell was the most popular of biology topic. This finding also indicated that Digestive System (DS) and Circulatory System (CS) and Features (KF) as the most chosen subject matter trends conducted by preservice teachers